El cine, lo audiovisual y sus itinerarios técnicos - Proyecto - Choi, Domin (2015)
Since the gestation of modern cinema and its theorization -particularly the one that Bazin derives from their techniques conditions- , there is a long way to contemporary cinema. This path can be thought from the adoption and film processing by a series of technological changes. Given the current conditions that brings about the invention of new digital technology we will, initially, attempt mutations, it means, the new conditions imposed by the digitization of cinema in both its aesthetics and its mode of production and dissemination. That is, the emergence of this new technology not only allows the making of unusual images, and increasingly rapid change, but also enables new forms of production, distribution and access. This situation must be inserted into a broader theoretical and historical context, taking some elements of the philosophy of art, art history, aesthetic theory, film criticism and film theory.